Histomorphological study of salivary gland neoplasms: fifteen year study - Hemalata, M.; Manjula, C. P.; Nandi, Rishitha (International Journal of Research in Medical Sciences, 2020)
Background: The neoplasms of salivary glands are relatively uncommon and represent less than 2% of all human tumors. They are morphologically diverse, with marked heterogeneity among the different subtypes and even within the same tumor. The unpredictability in the long term outcome imposes a significant challenge in the clinical management. Methods: This is a descriptive study done in a tertiary care teaching hospital over a period of 15 years. Patient details were collected from medical case records. All specimens were evaluated for site, laterality, size, nature of the cut surface and intactness of the capsule. Two to 5 representative bits were taken from each specimen and subjected to routine fixation, processing and section cutting followed by Haematoxylin and Eosin staining. Results: A total of 138 salivary gland tumors were diagnosed from patients in the age group of 13 to 90 years with a mean age of 41.8 years. There were 53 (38.4%) males and 85 (61.6%) females with male to female ratio of 1:1.42. There were 115 (83.3%) benign tumors and 23 (16.7%) malignant tumors. Pleomorphic adenoma accounted for 70.3% of all salivary gland tumors followed by mucoepidermoid carcinoma (10.9%), Warthin tumor (8%), basal cell adenoma (2.9%), adenoid cystic carcinoma (2.2%), squamous cell carcinoma (2.2%), myoepithelioma (1.4%), oxyphillic adenoma (0.7%), acinic cell carcinoma (0.7%) and salivary duct carcinoma (0.7%). Conclusions: The salivary gland neoplasms are relatively uncommon head and neck tumors. Parotid gland is the commonest site of occurrence. Pleomorphic adenoma is the commonest benign and mucoepidermoid carcinoma the commonest malignant salivary gland tumor.